Crafting the "myths of the future": the art and science of writing scenarios in scenario planning - Coons, Laura Marie, author; Chermack, Thomas, advisor; Chai, DaeSeok, committee member; Doe, Sue, committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2019)
The purpose of this research was to investigate scenario writing as a discrete component of the scenario planning process. While ongoing scholarship on scenario planning has added data to support many of the outcomes of the process, the specific guidance to writers of scenarios has remained largely absent from the literature. For those who would write scenarios either as practitioners or as organizational members who tackle the process, more information would be useful to inform the writing. This research had two aims. First, to distill the available literature on scenario writing into a practical model for writers. In addition to reviewing scenario planning literature, this work also considered the impact of specific genres of writing: science fiction, with its future-oriented frame; theater, with its performance and lived-experience approach to content; and short stories, with their high-impact, short-format structure. Beyond types of writing, best practices for writing were also considered. Second, this work sought to test writing quality in scenarios by measuring participant experiences with the stories. To accomplish this second objective, the researcher facilitated a series of scenario planning workshops, wrote scenarios of high and low quality, and leveraged the ITC-Sense of Presence Inventory (SOPI) to measure participant experiences of sense of presence. Sense of presence is a useful and previously unexplored construct to measure participant experiences with scenarios. The ITC-SOPI has primarily been used to measure sense of presence for participants experiencing non-written media, like movies, video games, or virtual reality. The tool showed promise, however, to asses a scenario reader's experience as well. The instrument measures four constructs of sense of presence: spatial presence, engagement, ecological validity, and negative effects. Spatial presence is a person's sense of being drawn into the medium. Engagement describes a participant's sense of enjoyment. Ecological validity is the sense of naturalness or realistic qualities of the medium. And negative effects are the person's discomfort experienced after interacting with the medium. All of these constructs are of interest to scenario writers, since the existing literature does consistently explain that participants should experience all four – feeling drawn into the story, enjoying at least parts of the experience, feeling that the scenarios are realistic, and potentially undergoing difficult or challenging changes in thinking as a consequence of the experience. The results of the inquiry were promising. Three hypotheses were tested to understand how scenario quality affected participant sense of presence and whether or not participating in the workshops had any effect on sense of presence. Results indicated that both workshop participation and scenario quality had statistically significant effects on sense of presence scores. Such results indicate additional inquiry would be beneficial.
Keywords: scenarios; writing; strategic planning; scenario planning